World monetary centres at the stage of global financial instability: risks, challenges and perspectives - Vishnevsky, V.P.; Shelud'ko, N.M. (Економіка промисловості, 2017)
The paper analyzes origins, challenges and risks, associated with global financial transformations and the aggravation of the national currencies competition, in order to improve the understanding of the changes, taking place in this sphere, and to determine prospects for the development of the world financial system. It is substantiated that, taking into account the actions of global fundamental factors (populational, civilizational, technological, allocative and financial) in the long term, the financial situation on the planet will remain unstable.Based on the application of the developed concept of the economic and monetary potential, it is grounded that in the medium term the world is likely to be generally divided into (if you ignore the British pound and the Japanese yen) the unstable predominant areas of US dollar (relatively stable), euro (decreasing), and RMB (increasing). The Russian ruble will remain on the world periphery and the potential growth of its influence will only be of a regional character. In general, the world will move to a multipolar financial architecture, the formation of which is connected with the "warming up" of new hotbeds of financial strains.Nevertheless, the US dollar will still remain the world’s leading currency for a long time (at least until the 2030s), due to the high political, military and economic influence of the USA, the relatively balanced monetary flows sources, the orientation of the economy on the large internal market, rather than on volatile external markets, as well as taking into account the "path dependence", in this case - the benefits of using the US dollar from the minimizing transaction costs standpoint.The paper also substantiates, that in the medium-term agenda, despite the fact that the leading central banks managed to pacify the global crisis of 2007-2008, to improve the prospects for the developed economies and to begin the processes of normalizing the monetary policy, there remain the following questions of: distorted financial asset values and high risks in the non-financial sector, which is being restructured on cyberphysical technologies; persistently low interest rates in many developed countries; overheated credit and securities markets; high levels of global and national debts; targeted use of national currencies in order to achieve unilateral trading advantages, new challenges, related to the restructuring of the financial intermediation sector under the influence of fintech, etc. This is exactly the modern "financial normality", under which turbulent processes of shaping the new political and economic structure of the world will take place in the forthcoming years. На основі застосування розробленого методичного підходу до оцінки економіко-монетарного потенціалу визначено ключові тренди сегментації світової фінансової архітектури. У середньостроковій перспективі (якщо абстрагуватися від британського фунта і японської ієни) вона буде представлена нестійкими зонами переважного впливу долара США - відносно стабільною, євро - що скорочуватиметься і юаня - що зростатиме. Російський рубль залишиться на світовій периферії, а очікуване посилення його впливу матиме переважно регіональний характер. Також визначено ключові ризики і виклики, що складають нинішню "фінансову нормальність", в умовах якої в майбутні роки буде формуватися нова політико-економічна структура світу. На основе применения разработанного методического подхода к оценке экономико-монетарного потенциала определены ключевые тренды сегментации мировой финансовой архитектуры. В среднесрочной перспективе (если абстрагироваться от британского фунта и японской иены) она будет представлена неустойчивыми зонами преимущественного влияния доллара США - относительно стабильной, евро - сокращающейся и юаня - растущей. Российский рубль останется на мировой периферии, а ожидаемый рост его влияния будет иметь преимущественно региональный характер. Также определены ключевые риски и вызовы, составляющие нынешнюю "финансовую нормальность", в условиях которой в предстоящие годы будет формироваться новая политико-экономическая структура мира.